Climate Change, Liberalism, an the Public/Private Distinction - Di Paola, Marcello; Jamieson, Dale W. (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
Climate change puts pressure on a distinction that is at the heart of liberal theory: that between the public and the private. Many of the GHG-emitting behaviors that contribute to the disruption of the climate system – such as using computers, taking hot showers, eating this or that, driving cars, investing here or there, and having children – are traditionally regarded as private. Yet today, through climate change, these apparently private behaviors can have very public consequences, however indirect, across spatial, temporal and genetic boundaries. The chapter introduces the public/private distinction and discusses the various ways in which it has figured in liberal theory. It goes on to show how climate change threatens the viability of the distinction, both by intensifying old tensions and by bringing new pressures to bear. It then consider some options for relieving the pressure, none of which seems particularly promising by liberal lights.